Optical-resolution photoacoustic microscopy of oxygen saturation with nonlinear compensation - Liu, Chao (Biomed Opt Express, 2019)
Optical-resolution photoacoustic microscopy (OR-PAM) of oxygen saturation (sO(2)) offers high-resolution functional information on living tissue. Limited by the availability of high-speed multi-wavelength lasers, most OR-PAM systems use wavelengths around 532nm. Blood has high absorption coefficients in this spectrum, which may cause absorption saturation and induce systematic errors in sO(2) imaging. Here, we present nonlinear OR-PAM that compensates for the absorption saturation in sO(2) imaging. We model the absorption saturation at different absorption coefficients and ultrasonic bandwidths. To compensate for the absorption saturation, we develop an OR-PAM system with three optical wavelengths and implement a nonlinear algorithm to compute sO(2). Phantom experiments on bovine blood validate that the nonlinear OR-PAM can improve the sO(2) accuracy by up to 0.13 for fully oxygenated blood. In vivo sO(2) imaging has been conducted in the mouse ear. The nonlinear sO(2) results agree with the normal physiological values. These results show that the absorption saturation effect can be compensated for in nonlinear OR-PAM, which improves the accuracy of functional photoacoustic imaging.